Freelancing and Labor in the Digital Economy - Sawyer, Steve; Dunn, Michael; Rancy, J.P.; Munoz, Isabel; Raheja, Raghav; Vaccaro, Gabrielle; Caruso, Alaina; Weller, Haley; Moffly, Lily (2020)
ABSTRACT With this position paper we encourage attention to one future of work: project-based, gig-, or freelancing workers who find their work online . Online freelancers and the online labor markets where they seek work are a relatively recent subset of the labor force and a new form of labor markets, seen by many as both a means to provide opportunities for workers seeking flexible employment arrangements - ‘gigs’ - and for organizations to help absorb market shocks (Gray and Suri, 2019; Kalleberg, 2003; Lehdonvirta et al., 2019). In the face of the economic upheaval due to the novel coronavirus, these workers and their online labor market are experiencing substantial changes. Keywords contingent work, knowledge work, freelance work, computerization, automation, labor markets, platforms, infrastructure ABOUT THE AUTHOR/S Steve Sawyer Syracuse University ssawyer@syr.edu "Steve Sawyer is on the faculty of Syracuse University’s iSchool. His research focuses on the changing forms of work and organizing enabled through uses of digital technologies. His work is done through detailed field-based studies that advance sociotechnical approaches to studying computing collectively known as social informatics. Prior to returning to Syracuse, Steve was a founding faculty member of the Penn State’s iSchool. https://ischool.syr.edu/people/directories/view/ssawyer/" Michael Dunn Skidmore College mdunn@skidmore.edu J.P. Rancy Syracuse University jrancy@syr.edu Isabel Munoz Syracuse University iimunoz@syr.edu Raghav Raheja Syracuse University rraheja@g.syr.edu Gabrielle Vaccaro Skidmore College gvaccaro@skidmore.edu Alaina Caruso Syracuse University agcaruso@syr.edu Haley Weller Syracuse University heweller@syr.edu Lily Moffly Syracuse University lmoffly@syr.edu New Future of Work ’20, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).